On the monetary union of the Gulf States - Shafik Hebous (Kiel Institute for the World Economy (IfW), 2006)
This paper attempts to highlight the main characteristics of the economies of the Gulf Cooperation Council (GCC) and their plan to form a monetary union by 2010. Several aspects are considered such as the pattern of trade, the monetary side, and the fiscal side. The main conclusion is that the large similarities among the GCC members reduce the costs of introducing a single currency while the small intra-trade volume reduces the benefits. Furthermore, in general the GCC states have achieved a noteworthy degree of convergence taking the European convergence criteria as a reference.
Keywords: 330